2021
DOI: 10.1016/j.jdent.2021.103723
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical performance and complications of zirconia-based tooth- and implant-supported fixed prosthodontic restorations: A summary of systematic reviews

Abstract: To present an overview on systematic reviews on prosthodontic zirconia restorations and to discuss long-term complications as well as information on anatomical and functional changes to the masticatory system. Data/Sources: MEDLINE, EMBASE, Trip medical, and Cochrane Library databases were searched for systematic reviews up to February 2021. Bias was assessed and clinical survival and complications were analyzed. Study selection: 38 eligible articles published between 2006 and 2021 were included. The reviews w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 80 publications
0
27
0
Order By: Relevance
“…In the literature, tooth-and implant-born monolithic zirconia restorations in nonbruxers have presented promising treatment outcomes for single crowns and multiunit fixed partial dentures [10,20]. A summary of systematic reviews on the long-term clinical performance and complications of zirconia-based tooth and implant-supported fixed prosthodontic restorations reported excellent 5-year cumulative survival rates despite a number of biological and technical complications [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, tooth-and implant-born monolithic zirconia restorations in nonbruxers have presented promising treatment outcomes for single crowns and multiunit fixed partial dentures [10,20]. A summary of systematic reviews on the long-term clinical performance and complications of zirconia-based tooth and implant-supported fixed prosthodontic restorations reported excellent 5-year cumulative survival rates despite a number of biological and technical complications [10].…”
Section: Discussionmentioning
confidence: 99%
“…A recent overview of systematic reviews on zirconia-based tooth and implant-supported restorations reported a 5-year satisfactory result with the predominant technical problem being veneering fractures [10]. However, the authors noted that patients with bruxism were examined only sporadically and that most of the studies to evaluate the survival and success of ceramic restorations have excluded bruxer patients as bruxism is considered a potential cause of restoration fracture [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Today, monolithic zirconia is a popular material for the fabrication of single crowns, short- and long-span fixed dental prostheses, and full-arch restorations [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Zirconia has been advocated as a valid treatment option for single-tooth restoration [ 2 , 3 , 4 , 5 , 8 ]. This is owing to its inherent esthetic and mechanical properties [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The material loss of the 4Y-TZP was noted to be considerably lower than that of the natural enamel antagonists. While minimum wear may in theory be desirable, the lower 2BW reported between enamel and zirconia in comparison with enamel-enamel contact points [ 32 ] may disbalance occlusion schemes and should be taken into account when planning a prosthetic restoration [ 33 ]. In contrast to earlier findings that reported high-speed sintering to result in less 2BW of 4Y-TZP than seen for a conventionally sintered control group [ 18 ], the choice of material/sintering protocol did not influence the reported material loss in the present investigation.…”
Section: Discussionmentioning
confidence: 99%